Analysis of Differentially Expressed Genes (DEG) and Upstream Regulator Proteins Indicates That Inhibition of Transforming Growth Factor Beta 1 (TGFB1) is A Potential Target for Acne Inversa - Veranita, Weri; Fauziah, Siva; Nurbaya, Siti (UI Scholars Hub, 2025)
Acne inversa (AI) is a chronic inflammatory skin disease characterized by painful nodules, abscesses, and scarring, primarily in intertriginous areas. This study aims to identify potential therapeutic targets for managing acne inversa based on the analysis of differentially expressed genes (DEG). The expression targets of these genes were then validated for their potential as biomarkers, and upstream regulator proteins (URPs) were identified from the resulting DEG. DEG analysis on the GEO dataset GSE122592 (acne inversa vs. healthy donor skin) revealed five DEG that can serve as biomarkers for acne inversa, with a sensitivity and specificity of (100%). These DEG—IL10, GZMB, FASLG, PRF1, and HLA-DPB10—are genes associated with autoimmune thyroiditis (AIT). AIT has previously been significantly linked to acne vulgaris. URP analysis indicates that inhibition of Transforming Growth Factor Beta 1 (TGFB1) is a therapeutic target that could be used to downregulate these five DEGs, returning their expression to healthy skin levels.